2011
DOI: 10.3945/jn.110.136747
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Prebiotic Mixture Added to Starting Infant Formula Has Long-Lasting Bifidogenic Effects

Abstract: There is some evidence that early colonization of the intestine affects the composition of the intestinal microbiota after weaning. In the present study, the effect of prebiotics administered from the first day of life on fecal counts of bifidobacteria and lactobacilli were studied during and after the administration of the prebiotics. In this double-blind, randomized, placebo-controlled, explorative study, 20 newborns of hepatitis C virus-infected mothers who decided not to breast feed due to their concerns r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 44 publications
0
52
0
Order By: Relevance
“…Of particular interest is how the intestinal microbiota is established, given the potential impact it has on subsequent health and disease (Reinhardt et al, 2009;Scholtens et al, 2012). Patterns of early intestinal colonization can have both short-term and long-term health effects (Bager et al, 2008;Cho et al, 2012;Collado et al, 2012;Kalliomäki et al, 2008;Salvini et al, 2011). Bacterial colonization of the intestine is key in several aspects: bacteria provide essential nutrients for the infant such as vitamins and short-chain fatty acids, they stimulate the development of the immune system, especially adaptive responses, and they provide general protection against pathogen colonization, among several other functions (Hooper et al, 2012;Nicholson et al, 2012).…”
Section: Establishment Of the Infant Intestinal Microbiotamentioning
confidence: 99%
“…Of particular interest is how the intestinal microbiota is established, given the potential impact it has on subsequent health and disease (Reinhardt et al, 2009;Scholtens et al, 2012). Patterns of early intestinal colonization can have both short-term and long-term health effects (Bager et al, 2008;Cho et al, 2012;Collado et al, 2012;Kalliomäki et al, 2008;Salvini et al, 2011). Bacterial colonization of the intestine is key in several aspects: bacteria provide essential nutrients for the infant such as vitamins and short-chain fatty acids, they stimulate the development of the immune system, especially adaptive responses, and they provide general protection against pathogen colonization, among several other functions (Hooper et al, 2012;Nicholson et al, 2012).…”
Section: Establishment Of the Infant Intestinal Microbiotamentioning
confidence: 99%
“…161 It was also noted that specific combinations of prebiotics, including short chain (sc) GOS/long chain (lc) FOS, increased bifidobacteria and lactobacilli levels to the extent that, in some cases, levels of these genera were comparable to those observed in the gut of breastfed infants. 106,[162][163][164][165] This impact was apparent despite the fact that these prebiotics had structures, which differed from those of HMOS. In one such study qPCR and FISH were used in combination to identify and quantify the bifidobacteria in fecal samples from infants fed GOS and FOS supplemented feeds.…”
Section: Prebioticsmentioning
confidence: 91%
“…The majority of published studies 7-14 demonstrated significantly higher levels of bifidobacteria after supplementation, while two trials 15,16 reported a higher count of bifidobacteria; however this was not statistically significant. Salvini et al 17 in their small explorative study (sample size 20) reported a long-lasting bifidogenic effect, which continued even 6 months after intervention was stopped. One study looked at the difference in the stool colonies of bifidobacteria in infants fed on prebiotic-supplemented formula and breast-fed infants and found that formula supplemented with prebiotics has a bifidogenic effect comparable to that of breast milk.…”
Section: Stool Colonization With Bifidobacteria (Bifidogenic Effect)mentioning
confidence: 99%